Musculoskeletal Ultrasound to Identify Subclinical Joint and Periarticular Involvement in Patients With Inflammatory Bowel Disease: A Systematic Literature Review - Sakellariou, Garifallia; Schiepatti, Annalisa; Scalvini, Davide; Lusetti, Francesca; Fazzino, Erica; Biagi, Federico; Montecucco, Carlomaurizio (Frontiers in Medicine, 2022)
Background: Musculoskeletal ultrasonography identifies subclinical joint and entheseal inflammation, and it might be of value in patients with inflammatory bowel diseases (IBD), which are at higher risk of inflammatory arthropathy and disability. Our aim was to retrieve the evidence on the applications of ultrasound in patients with non-arthropathic IBD. Methods: Studies enrolling patients with IBD without arthritis, undergoing ultrasound of joints, tendons or entheses were eligible. The outcomes of interest encompassed the frequency of ultrasound-detected lesions, their accuracy in diagnosing arthritis, their prognostic role and sensitivity to change. All study types, excluding case reports, case series and narrative reviews, were included. Search strategies were applied in PubMed and Embase. Abstract and full-texts were evaluated by pairs of reviewers. The risk of bias was evaluated through the Newcastle-Ottawa scale or the Quality Assessment of Diagnostic Accuracy Studies (QUADAS) 2. The protocol was registered in PROSPERO (CRD42021264972). Results: Out of 2304 records, 8 studies were included, all reporting the frequency of lesions, while only 3 evaluated also the diagnostic accuracy. All studies had a cross-sectional design, with no evidence on prediction or follow-up. All studies evaluated the entheses, while only 3 the joints. The most common chronic lesions were entheseal thickening (up to 81.5%) and enthesophytes (67.9%), while entheseal erosions were present in 16-17% of patients. Among inflammatory lesions, power Doppler was reported in 14-67% of patients. There were no differences among Crohn’s disease or ulcerative colitis and depending on disease activity, while there were contrasting results on different disease durations. When evaluating the diagnostic performance, the best specificity for a diagnosis if IBD was 0.88 (95%CI, 0.8-0.94) for joint abnormalities. Also, the best sensitivity was 0.88 (95%CI, 0.76-0.95) for entheseal lesions. No studies assessed of the combination of lesions. Due to the limited number of studies, meta-analyses were not performed. Conclusions: Despite the possible value of ultrasound in IBD, there is limited evidence deriving from cross-sectional studies. Longitudinal studies are needed to clarify the role of this technique, while its current placement might be that of complementing clinical assessment, in particular in early intestinal disease.